Isolation and Identification of Contaminant Molds on Pumpkin Candy from Sumbawa Besar - Utami Sri Hastuti; Linda Hapsari; Henny Nurul Khasanah (Universitas Sebelas Maret, 2015)
Pumpkin candy is a sort of pumpkin fruit processed products that is typical food from Sumbawa Besar. Pumpkin candy contains carbohydrates, fats, protein, fiber, and minerals. The mold can contaminate and degradate the pumpkin candy compounds, thus lowering the quality of the pumpkins candy. The purpose of this research were: 1) to identify the species of contaminant mold on candy pumpkin; 2) to determining the most dominant species on the pumpkins candy. The research were conducted at the Microbiology Laboratory, Departement of Biology, State University of Malang. The pumpkin candy sample was from Sumbawa Besar. The samples stored in a sterile jar for 8 days. The 25 grams of pumpkin candy were granded, then dissolved in 225 ml of 0,1% peptone to obtain a suspension with a dilution rate 10-1. Then the suspension is diluted again gradually in order to obtain a suspension with a dilution rate 10-2, 10-3, 10-4, 10-5, and 10-6. The suspension on each level of dilution was inoculated on a medium plate Czapek Agar (CA), and then incubated at 25-27oC for 7x24 hours. Identification contaminant molds was done by observing the colony morfology and microscopic characteristic then referred to the book of mold identification. The results showed: 1) there are 11 species of contaminants mold that grow in pumpkin candy. The contaminant mold species are Aspergillus terreus Thorn, Penicillium brevicompactum Dierckx, Penicillium paraherquei Abe ex G. Smith, Aspergillus niger Van Tieghem, Penicillium frequetans Westling, Aspergillus candidus Link, Cladosporium herbarum (Pers.) Link ex Gray, Cladosporium cladosporioides (Fres.) de Vries, Nigrospora oryzae, Penicillium verrucosum Dierckx var corymbeferum (Westling) Samson et al., and Penicillium camemberti Thorn; 2) the dominant contaminant mold species in pumpkin candy samples is Cladosporium.